Comparison of real time PCR and conventional PCR by identifying genomic DNA of bovine and porcine - Muhammad Abdurrahman Munir; Ahlam Inayatullah (Jurnal Kimia Terapan Indonesia, 2021)
Bovine and porcine are poultry meat that consumed worldwide particularly in Southeast Asia.Both of them are prone to food counterfeit owing to several factors such as price, appetite and Halal status. Sensitive and selective analytical methods are required to control meat products that distributed to markets. This paper studied the sensitivity between real – time and conventional PCR or known as qPCR and cPCR, respectively. Bovine and porcine were samples used to verify the sensitivity of them. Nevertheless, those instruments did not show a specific difference during DNA analysis of bovine and porcine. In conventional PCR, two pairs of DNA primers targeted cytochrome b (Cyt b) was analyzed, resulting of 120 and 131 amplicons, respectively. While qPCR applied to analyze porcine and bovine DNA. The detection limit of qPCR after porcine and bovine analysis were at 0.004 and 0.007 µg/µL, respectively. Results demonstrated the qPCR was reliable for verifying porcine and bovine DNA compared to conventional PCR. Furthermore, the study concluded that the developed assay can be easily employed for the identification of porcine and bovine tissue in food products in low resource areas.